Enhancing Teachers’ Competence in Developing PISA-Based Assessment Items Through Jumping Task Training at Al-Arief Islamic Senior High School - Nusantara, Duano Sapta; Gustiningsi, Tria; Pasaribu, Feri Tiona; sainuddin, syamsir; Junita, Ranisa; Ramalisa, Yelli; Isnania, Isnania (Jurnal Karya Abdi Masyarakat, 2026)
This community service program aimed to enhance teachers’ understanding of the conceptual framework of the Programme for International Student Assessment (PISA) and improve their skills in developing locally contextualized assessment items. The activity responded to teachers’ limited ability to design questions requiring critical thinking and problem-solving, as well as their lack of experience in applying contextual tasks in classrooms. The program involved conceptual framework dissemination, training and mentoring on item development, classroom implementation, and evaluation through pre-tests, post-tests, response sheets, and classroom observations. Twenty-one participants, including teachers from Al-Arief Islamic schools and students from Jambi University, actively engaged in all stages. Results showed an increase in average scores from 2.62 to 4.04, with an N-Gain of 0.60 (moderate). Teachers’ knowledge, experience with assessment tasks, and problem-solving strategies all improved significantly. The novelty lies in integrating local contexts into item design, which strengthened teachers’ conceptual understanding and readiness for classroom implementation. The training proved effective in building teachers’ capacity and supporting more relevant and contextual teaching practices.